Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1974
DOI: 10.3323/jcorr1974.23.8_385
|View full text |Cite
|
Sign up to set email alerts
|

Grooving Corrosion on ERW Steel Pipe in Sea Water

Abstract: The grooving corrosion mechanism of an ordinary electric resistance welded (ERW) carbon steel pipe in sea water was investigated using electrochemical and microscopic observation techniques. Deep grooving corrosion was observed to occur at the narrow welded parts after rotating immersion test in sea water at 40C for one year, and no grooving corrosion was observed in the matrix of the pipe. Potential measurement using micro-electrode showed that the potential of the weld was ca. 70mY lower than that of the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The difference of the open-circuit potential is a maximum of $ 70 mV [35]. The more negative, or less noble, potential of the weld seam has been attributed to the formation of unstable MnS inclusions in the weld by the thermal cycle of the welding operation [36,37]. Butt-welded pipes that have been heated uniformly in the process of shaping and welding are not susceptible to this type of corrosion.…”
Section: C3 Groove Corrosion Of Electric Resistance Welded Pipementioning
confidence: 98%
“…The difference of the open-circuit potential is a maximum of $ 70 mV [35]. The more negative, or less noble, potential of the weld seam has been attributed to the formation of unstable MnS inclusions in the weld by the thermal cycle of the welding operation [36,37]. Butt-welded pipes that have been heated uniformly in the process of shaping and welding are not susceptible to this type of corrosion.…”
Section: C3 Groove Corrosion Of Electric Resistance Welded Pipementioning
confidence: 98%
“…It is reported 23) that the reaction proceeds at 1100 C, judging from the free energy. In Electric-Resistance-Welded (ERW) steel pipe, a sulfurenriched phase 29) on the surface of MnS has been reported in relation to grooving corrosion, although more than 0.1% Cu is added. These investigators have not identified its phase crystallographically and stoichiometrically, but we surmise that it could be Cu-S.…”
Section: 3mentioning
confidence: 99%